Comparative Effectiveness of Initial Treatment for Infantile Spasms in a Contemporary US Cohort. (21st September 2021) - Grinspan, Zachary M.; Knupp, Kelly G.; Patel, Anup D.; Yozawitz, Elissa G.; Wusthoff, Courtney J.; Wirrell, Elaine C.; Valencia, Ignacio; Singhal, Nilika S.; Nordli, Douglas R.; Mytinger, John R.; Mitchell, Wendy G.; Keator, Cynthia G.; et al.
Abstract : Objective: To compare the effectiveness of initial treatment for infantile spasms. Methods: The National Infantile Spasms Consortium prospectively followed up children with new-onset infantile spasms that began at age 2 to 24 months at 23 US centers (2012–2018). Freedom from treatment failure at 60 days required no second treatment for infantile spasms and no clinical spasms after 30 days of treatment initiation. We managed treatment selection bias with propensity score weighting and within-center correlation with generalized estimating equations. Results: Freedom from treatment failure rates were as follows: adrenocorticotropic hormone (ACTH) 88 of 190 (46%), oral steroids 42 of 95 (44%), vigabatrin 32 of 87 (37%), and nonstandard therapy 4 of 51 (8%). Changing from oral steroids to ACTH was not estimated to affect response (observed 44% estimated to change to 44% [95% confidence interval 34%–54%]). Changing from nonstandard therapy to ACTH would improve response from 8% to 39% (17%–67%), and changing to oral steroids would improve response from 8% to 38% (15%–68%). There were large but not statistically significant estimated effects of changing from vigabatrin to ACTH (29% to 42% [15%–75%]), from vigabatrin to oral steroids (29% to 42% [28%–57%]), and from nonstandard therapy to vigabatrin (8% to 20% [6%–50%]). Among children treated with vigabatrin, those with tuberous sclerosis complex (TSC) responded more often than others (62% vs 29%; p < 0.05). Discussion: Compared to nonstandard therapy, ACTH and oral steroids are superior for initial treatment of infantile spasms. The estimated effectiveness of vigabatrin is between that of ACTH/oral steroids and nonstandard therapy, although the sample was underpowered for statistical confidence. When used, vigabatrin worked best for TSC. Classification of Evidence: This study provides Class III evidence that for children with new-onset infantile spasms, ACTH or oral steroids were superior to nonstandard therapies.